Analisis Yuridis Keterbatasan Penegakan Hukum Terhadap Kejahatan Perdagangan Manusia Transnasional (Studi Kasus Human Traffic di Kamboja) - Lazarus L; Muhammad Rahmadzani Hidayat; Qurrotul Aini; Raisya Syafira Zahra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study conducts a juridical analysis of the limitations in law enforcement against transnational human trafficking (TPPO), focusing on the case study of Indonesian citizens (WNI) exploited in Cambodia through online fraud schemes (scam compounds). Although both Indonesia and Cambodia are bound by international (UNTOC, Palermo Protocol) and regional (ACTIP, MLAT) legal instruments, the effectiveness of cross-border cooperation remains far from optimal. The research identifies major obstacles stemming from inconsistencies in the legal definitions of TPPO and standards of proof, weak mechanisms for extradition and Mutual Legal Assistance (MLA), and inadequate information exchange. Specifically in Cambodia, enforcement is hampered by the inconsistent application of the 2008 TSE Law, insufficient victim protection, and high levels of structural corruption. Using a normative juridical approach, this study concludes that human trafficking, as an extraordinary crime, cannot be addressed unilaterally. It requires strengthened and integrated international cooperation including the optimization of MLA, extradition, the formation of Joint Investigation Teams (JITs), and the harmonization of regulations at the ASEAN level to close legal loopholes and enhance the justice response. Recommendations include improving the capacity of investigators, standardizing TPPO definitions, and establishing comprehensive victim protection mechanisms.